Teachers' views on optimizing Kurikulum Merdeka in SMK Kencana accounting department - Mumtaz Ali Ridha Al Munawar; Nayla Ikhsani Azyan; Stephanie Aurelia; Sulis Indriani; Angga Hadiapurwa (Hipkin Journal of Educational Research, 2025)
Curriculum transformation represents a strategic initiative the government took to improve the quality of learning, adjusting to the needs of an ever-evolving era. The Kurikulum Merdeka, present as an educational innovation, is designed to provide schools with freedom to achieve relevant learning objectives. This study aims to analyze the management of Kurikulum Merdeka at SMK Kencana, especially in the Accounting department, to support a quality learning system. This research uses a qualitative approach with in-depth interview techniques with school management to explore experiences, challenges encountered and strategies employed during curriculum implementation. The results showed that curriculum management at SMK Kencana has improved significantly, both from the perspective of teachers and school management. SMK Kencana successfully implemented Kurikulum Merdeka in the AKL department through subject integration, experiential projects, and collaboration with industry. This curriculum enhances teacher innovation, learning, and the relevance of materials to work needs. Despite adaptation challenges, this implementation effectively supports students' readiness for the world of work. This study concludes that the synergy between teachers and school management is the key to optimizing the management of Kurikulum Merdeka. These findings provide practical recommendations for further development in curriculum implementation in a Vocational High School environment, especially the Accounting Department.   Abstrak Perubahan kurikulum merupakan langkah strategis yang dilakukan oleh pemerintah untuk meningkatkan mutu pembelajaran, menyesuaikan dengan kebutuhan zaman yang terus berkembang. Kurikulum Merdeka, hadir sebagai inovasi pendidikan, dirancang untuk memberikan kebebasan kepada sekolah dalam mencapai tujuan pembelajaran yang relevan. Penelitian ini bertujuan untuk menganalisis pengelolaan Kurikulum Merdeka di SMK Kencana, khususnya pada jurusan Akuntansi, guna mendukung sistem pembelajaran berkualitas. Penelitian ini menggunakan pendekatan kualitatif dengan teknik wawancara mendalam kepada manajemen sekolah untuk menggali pengalaman, tantangan, serta strategi yang diterapkan selama implementasi kurikulum. Hasil penelitian menunjukkan bahwa pengelolaan kurikulum di SMK Kencana telah mengalami peningkatan signifikan, baik dari perspektif pendidik maupun manajemen sekolah. SMK Kencana berhasil menerapkan Kurikulum Merdeka di jurusan AKL melalui integrasi mata pelajaran, proyek berbasis pengalaman, dan kolaborasi dengan dunia industri. Kurikulum ini meningkatkan inovasi pendidik, pembelajaran, dan relevansi materi dengan kebutuhan kerja. Meskipun ada tantangan adaptasi, penerapan ini efektif mendukung kesiapan peserta didik menghadapi dunia kerja. Penelitian ini menyimpulkan bahwa sinergi antara pendidik dan manajemen sekolah menjadi kunci utama dalam mengoptimalkan pengelolaan Kurikulum Merdeka. Temuan ini memberikan rekomendasi praktis untuk pengembangan lebih lanjut dalam penerapan kurikulum di lingkungan Sekolah Menengah Kejuruan, khususnya Jurusan Akuntansi. Kata Kunci: akuntansi; kurikulum merdeka; optimalisasi kurikulum; pengelolaan kurikulum